Wnt9a Promotes Renal Fibrosis by Accelerating Cellular Senescence in Tubular Epithelial Cells - Luo, Congwei; Zhou, Shan; Zhou, Zhanmei; Liu, Yahong; Yang, Li; Liu, Jiafeng; Zhang, Yunfang; Li, Hongyan; Liu, Youhua; Hou, Fan Fan; Zhou, Lili (Journal of the American Society of Nephrology, 2018)
Cellular senescence is associated with renal disease progression, and accelerated tubular cell senescence promotes the pathogenesis of renal fibrosis. However, the underlying mechanism is unknown. We assessed the potential role of Wnt9a in tubular cell senescence and renal fibrosis. Compared with tubular cells of normal subjects, tubular cells of humans with a variety of nephropathies and those of several mouse models of CKD expressed high levels of Wnt9a that colocalized with the senescence-related protein p16 INK4A . Wnt9a expression level correlated with the extent of renal fibrosis, decline of eGFR, and expression of p16 INK4A . Furthermore, ectopic expression of Wnt9a after ischemia-reperfusion injury (IRI) induced activation of β -catenin and exacerbated renal fibrosis. Overexpression of Wnt9a exacerbated tubular senescence, evidenced by increased detection of p16 INK4A expression and senescence-associated β -galactosidase activity. Conversely, shRNA-mediated knockdown of Wnt9a repressed IRI-induced renal fibrosis in vivo and impeded the growth of senescent tubular epithelial cells in culture. Notably, Wnt9a-induced renal fibrosis was inhibited by shRNA-mediated silencing of p16 INK4A in the IRI mouse model. In a human proximal tubular epithelial cell line and primary renal tubular cells, Wnt9a remarkably upregulated levels of senescence-related p16 INK4A , p19 ARF , p53, and p21 and decreased the phosphorylation of retinoblastoma protein. Wnt9a also induced senescent tubular cells to produce TGF- β 1, which promoted proliferation and activation in normal rat kidney fibroblasts. Thus, Wnt9a drives tubular senescence and fibroblast activation. Furthermore, the Wnt9a–TGF- β pathway appears to create a reciprocal activation loop between senescent tubular cells and activated fibroblasts that promotes and accelerates the pathogenesis of renal fibrosis.